Modeling of interior beam-column joints for nonlinear analysis of reinforced concrete frames. (1st July 2017) - Pan, Zhangcheng; Guner, Serhan; Vecchio, Frank J.
Highlights: Component-based models are suitable for implementation into nonlinear frame analysis. The implemented joint element simulates the joint shear deformations and bar-slip effects. Modifications of the global procedure are required to facilitate the implementation. Joints can be modeled with the specification of material and geometric properties. The program showed reasonably good accuracy in the analysis of joint subassemblies. Abstract: Beam-column connections undergo significant shear deformations and greatly contribute to story drifts during earthquake loading, yet their response is typically neglected in traditional frame analyses through the use of rigid end offsets. Although local joint models are available in the literature for the investigation of single, isolated joints, there is a lack of holistic frame analysis procedures simulating the joint behavior in addition to important global failure modes such as beam shear, column shear, column compression, and soft story failures. The objective of this study is to capture the impact of local joint deformations on the global frame response in a holistic analysis by implementing a joint model into a previously-developed global frame analysis procedure. The implemented joint element simulates the joint shear deformations and bar-slip effects. Concrete confinement effects are also considered so that both older and modern joints can be modeled. The developed procedure successfully captures the local load-deflection response of joints within a global frame analysis procedure. The ratio of predicted and observed peak load had a mean of 1.25 before the modification, and a mean of 1.05 after the modification.